Assessing the legislative politics in the making of the Foreign Bank Liberalization Act - Brillo, Bing Baltazar C. (2012)
The study is about the dynamics among the actors in the making of the Foreign Bank Liberalization Act or Republic Act 7721. The central issue in the legislation was whether to have a restricted or extensive liberalization of the banking sector. The policy divide was between the Senate-BSP-BAP-resident foreign banks' bloc, which was advocating for a single-mode of entry for foreign banks, and the House-FCCP-the rural-development banks-the academic-business-consumer groups' bloc, which was endorsing a multiple-mode of entry for foreign banks. The Senate-BSP-BAP-resident foreign banks' bloc prevailed since this bloc benefited from three intertwined factors in the legislation process. First, the inevitability of the liberalization of the banking sector left the domestic commercial banks with no recourse but to take an all-out effort to push for a limited liberalization law. Second, the Senate-BSP-BAP-resident foreign banks' bloc was aided by the collective action dilemma among the actors. And third, the internal dynamics among the members of the Senate and the House made it very difficult for the former and tolerable for the latter to compromise.
Keywords: Republic Act No. 7721; Banks and banking, Foreign -- Laws and legislation; Banking law